Using Orthorhombic Lattice Boltzmann Model to Research the Liquid Transport in Gas Diffusion Layer with Different Micro Porous Layer Coated (Communications in Computational Physics, 2020)
Water management in gas diffusion layer (GDL) and micro porous layer(MPL) poses a great impact on performance of proton exchange membrane fuel cells(PEMFCs). And enhancement of the performance of fuel cells requires an appropriatewater balance between the conservation of membrane humidity and the discharge ofexcess water produced in the cell. The Lattice Boltzmann method (LBM) can enablemore straight simulation of fluid flow with complex solid structures, compared withconventional computational fluid dynamics (CFD) method based on Navier-Stokesequations. In this study, the orthorhombic pseudo-potential multiphase lattice Boltzmannmethod (LBM) is used to investigate liquid water transport in the MPL and GDLof polymer electrolyte membrane fuel cells (PEMFC). And the GDL and MPL structureimages are all acquired by the stochastic generation method. We compared the GDLcoated by the MPL with different thickness and different porosity. Numerical resultsconfirm that influence of porosity is much greater than the thickness, which can helpto improve the GDL and MPL design.
Keywords: Proton exchange membrane fuel cell; lattice Boltzmann method; stochastic generation method; water management; gas diffusion layer; micro porous layer.